2008
DOI: 10.1007/s10745-008-9176-3
|View full text |Cite
|
Sign up to set email alerts
|

“Berry Patch” As a Kind of Place—the Ethnoecology of Black Huckleberry in Northwestern Canada

Abstract: The Gitksan and Wet'suwet'en of Northwestern British Columbia formerly used landscape burning to manage patches of black huckleberry (Vaccinium membranaceum), the most important plant resource of their seasonal round. In view of its significance one might postulate that managed sites would conform to a biophysical or ecological type to maximize return for effort. However, a survey of a number of traditionally managed sites indicated that managed sites are characterized by wide variation in biophysical attribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 18 publications
1
39
0
Order By: Relevance
“…pacifica; Deur 2005). Terrestrial resources including various shrubs and trees were also tended, pruned, and fertilized to increase berry and fruit production (Thornton 1999, Trusler andJohnson 2008). Landscapes were routinely cleared and burned to promote the productivity of successional plant species (Boyd 1999, Lepofsky et al 2005a, such as the underground edible bulbs of camas (Camassia spp.…”
mentioning
confidence: 99%
“…pacifica; Deur 2005). Terrestrial resources including various shrubs and trees were also tended, pruned, and fertilized to increase berry and fruit production (Thornton 1999, Trusler andJohnson 2008). Landscapes were routinely cleared and burned to promote the productivity of successional plant species (Boyd 1999, Lepofsky et al 2005a, such as the underground edible bulbs of camas (Camassia spp.…”
mentioning
confidence: 99%
“…However, it has been shown that the positions of resource locales in the landscape were also based on socioeconomic factors, such as proximity to other resources or distance to other important structures, such as villages or paths (Trusler & Johnsson 2008). This indicates that native people planned their extraction of resources and chose areas for extraction that fitted into a larger network of activities, resources and facilities.…”
Section: Land Use Matrixmentioning
confidence: 99%
“…In conclusion, pond fishing involves an exchange of trophic relationships between entities linked together by kin relationships. These interactions are mediated by agents of the human and spiritual worlds: the lineage head will receive the proscriptions and prescriptions of the spirits through dreams, (Fay 1989a, Fay 1989b, Ingold 2000, Pagezy 2006, Trusler and Johnson 2008, Descola 2011, Reo and Whyte 2012, Shepard 2014. A broadly shared vision is that animals give themselves, or are given by supernatural entities, to hunters and fishermen (Levy-Bruhl 1963;Pagezy 2006;Reo and Whyte 2012).…”
Section: Conclusion 59mentioning
confidence: 99%